KOORDINASI RELAY OCR, GFR DAN RECLOSER PASCA UPRATING TRANSFORMATOR TENAGA PADA PENYULANG MJO 01 GARDU INDUK MOJOSONGO - Ilyas Habil Agnia, - (2022)
Electrical energy is a very important resource. All human activities can not be separated from electrical energy. PT PLN is required to provide good service by ensuring the continuity of electricity distribution to consumers so that the electrical power reliability system can be maintained The reliability parameter of the electricity can be seen by the frequent of interrupts/blackouts occurred. Blackouts can be caused by the short circuit in the power system. To minimalize the short circuit, it needs a protection system which is well-coordinated from the power plants to the distribution lines. The study of protection system coordination on feeder MJO 01 from Gardu Induk Mojosongo is written in this paper using manual calculations and simulations on the ETAP 16.0.0 application.The aims of this study is to know the magnitude of short circuit that occurred on the lines, that it can be used to calculate the current and time setting of the OCRs, GFRs and reclosers. The coordination setting of relays in this paper is located on the incoming feeder, outgoing feeder, and recloser.The best coordination of the protection system is the coordination which each relay can be worked in sequence, without overlap occurred from the feeder to the incoming feeder. The result of this study is the time setting (tripping time) of the relays from the recloser to the incoming feeder is increasing and the overlapping is not occurred.